Possibilities of Amazon AWS and Google GCP cloud services in specific usecases - Michálek, Ondřej; Bruckner, Tomáš, 1974-; Dohnal, Václav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
Cloud IaaS providers that target enterprise and midmarket customers generally offer a high-quality service, with excellent availability, good performance, high security and good customer support. This group of providers contain Amazon Web Services who pioneered the cloud IaaS market in 2006 and also Google Cloud Platform who entered the cloud IaaS market in 2012.Work aims to analyze and differentiate three services which these providers offer to customers:* Virtual machines and their usage in server scaling (AWS Elastic Compute Cloud, GCP Compute Cloud)* Storage used while file sharing (AWS Simple Storage Service, GCP Storage)* Access Management of services and data (AWS IAM, GCP IAM)All of these three chapters contain detailed introduction of the service, the concept it roofs and detailed comparison of steps needed to set-up such services. This is needed for analysing the differences and similarities of provided services and serves two purposes:* Comparison of services provided by these provides * Evaluation of why is AWS more popular than GCP and if customers should choose either of them
Vedoucí práce: Tomáš Bruckner
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses